Cytotoxic compounds against cancer cells from Bombyx mori inoculated with Cordyceps militaris. Issue 6 (3rd June 2017) - Qiu, Weitao; Wu, Jing; Choi, Jae-Hoon; Hirai, Hirofumi; Nishida, Hiroshi; Kawagishi, Hirokazu
Abstract: Two compounds, 3′-deoxyinosine and cordycepin, were isolated from Bombyx mori inoculated with Cordyceps militaris . In the bioassay examining cytotoxicity against cancer cells, both compounds showed toxicity against A549, PANC-1, and MCF-7 cancer cells.